2015
DOI: 10.3748/wjg.v21.i9.2677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of longer battery life on small bowel capsule endoscopy

Abstract: Extending the operating time of CE may be a simple method to improve completion rate although it does not affect the rate of positive findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Fortunately, newer-generation capsules have longer battery life (>12 vs 8 hours with first-generation capsules), which may increase the duration of the study and completion rates. 123,124 Capsule retention has been reported in approximately 1.4% of CE procedures. 120,121,[125][126][127] Retrospective studies have reported retention rates of 0% to 1.6% in patients with suspected IBD, and of 5.2% to 13% in patients with known IBD.…”
Section: Contraindications Cautions and Consentmentioning
confidence: 99%
“…Fortunately, newer-generation capsules have longer battery life (>12 vs 8 hours with first-generation capsules), which may increase the duration of the study and completion rates. 123,124 Capsule retention has been reported in approximately 1.4% of CE procedures. 120,121,[125][126][127] Retrospective studies have reported retention rates of 0% to 1.6% in patients with suspected IBD, and of 5.2% to 13% in patients with known IBD.…”
Section: Contraindications Cautions and Consentmentioning
confidence: 99%
“…The progress of battery technology and robust computational frame interpolation techniques can mitigate problems with the current CCE capsules. CCE needs to be small enough to be swallowable, and the battery needs to last more than 8 h [24] . The transmission of the image data occupies about 90% of the total Fig.…”
Section: Future Direction: Cce Video Frame Interpolationmentioning
confidence: 99%
“…The main drawbacks of the oldgeneration capsules were their limited battery life, with up to 25% of them not reaching the colon during recording, a disadvantage that is almost eliminated with the development of capsules with a longer battery life, namely, EndoCapsule 10, MiroCam, Pillcam SB2-ex [20,21] and SB3, as well as the fear of capsule retention.…”
Section: Introductionmentioning
confidence: 99%